Linking Instructional Supervision to Teacher Development and School Growth in Early-Stage Islamic Elementary Institutions - Sahbana Ridha; Aslamiah Aslamiah; Noorhapizah Noorhapizah; Novitawati Novitawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Academic supervision is crucial for shaping teacher quality in educational institutions, yet its implementation in newly established Islamic schools remains underexplored. Most research focuses on established schools, creating a critical gap in understanding supervision's role during the formation phase when institutional culture and teacher adaptation are developing. This study addresses this gap by exploring academic supervision at SD Al-Halaby Islamic School, an early-stage Islamic elementary school operating for three years. Employing a descriptive qualitative approach with triangulation, semi-structured interviews, online questionnaires, and documentation analysis, all active teachers (n=25) participated through total sampling, supported by key informants including the principal, foundation board, parents, and community figures. Findings reveal that 92% of teachers reported supervision facilitated adaptation to the Islamic vision, 84% showed pedagogical improvements, and 96% preferred collaborative-reflective models. Challenges include psychological tension (72% initially), time constraints (80%), and nascent supervision culture (44%). Unlike established schools where supervision refines practices, this study demonstrates that supervision in early-stage Islamic schools functions dually as a socialization mechanism and a development tool, contributing to 1,045% enrollment growth. Results underscore that strengthening supervisory capacity as a core strategy not only improves learning quality but accelerates systemic institutional growth, building foundations for reputation and sustainability